Kosovo Country Economic Memorandum, November 2021 : Boosting Foreign Direct Investment - World Bank (World Bank, Washington, DC, 2022)
Foreign direct investment (FDI) can bring many benefits to Kosovo’s economy, creating more and better jobs and spurring greater and more resilient economic growth. Many transition economies have used FDI as a pillar of their structural transformation and modernization efforts. The small number of firms in Kosovo that include FDI are more productive than other firms, and they were more resilient in the wake of the Coronavirus disease 2019 (COVID-19) economic recession. In Kosovo, FDI inflows have been concentrated in sectors that provide limited potential for productivity spillovers and benefits to the domestic economy. Kosovo needs to adopt proactive policies to strengthen its investment competitiveness and investor outreach in order to unlock more and higher-quality FDI. This note presents an ambitious reform agenda that can help improve Kosovo’s investment competitiveness and investor outreach. It presents a step-by-step reform program for unlocking the full potential of FDI for economic growth and job creation in Kosovo that the government can implement in the short to medium term. The note is structured in three sections. The first section looks at Kosovo’s FDI performance and assesses the quantity and quality of the FDI attracted so far. The second section benchmarks Kosovo’s locational FDI determinants, considering a set of macroeconomic and microeconomic indicators for its overall FDI competitiveness. The third section combines the findings from the first two sections with an in-depth assessment of Kosovo’s policy, legal, and institutional framework for investment to present a targeted reform agenda and policy action plan to help attract more and higher-quality investments to Kosovo.